2018
DOI: 10.6026/97320630014521
|View full text |Cite
|
Sign up to set email alerts
|

Colony Collapse Disorder (CCD) in Honey Bees Caused by EMF Radiation

Abstract: Honey bees are one of the treasures in the world. An increase of waveform communication leads to good information exchange of mankind. In the biological view, it causes a lot of side effects and lifestyle changes in other living organisms. The drastic changes are causing the natural imbalance in the ecosystem and become a global issue. There are significant reasons for bee colony collapse disorder (CCD) like pesticides, disease and climate change. Recent studies reveal that a cell phone tower and mobile phone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…According to certain studies, honeybees do not rely on the electromagnetic field (EMF) to navigate, and many apiaries that are experiencing losses are in rural areas where cell phone service is absent. The World Health Organization confirmed the same data; however, some researchers revealed that there was standard evidence that the EMF could cause damage in honeybees [ 95 , 96 ]. It was associated with increased bees activity, increased inside temperature, increased queen loss, abnormal real cell production, weight loss, and reduced operculated brood [ 97 ].…”
Section: Main Causes Of Honeybee Colony Lossesmentioning
confidence: 69%
“…According to certain studies, honeybees do not rely on the electromagnetic field (EMF) to navigate, and many apiaries that are experiencing losses are in rural areas where cell phone service is absent. The World Health Organization confirmed the same data; however, some researchers revealed that there was standard evidence that the EMF could cause damage in honeybees [ 95 , 96 ]. It was associated with increased bees activity, increased inside temperature, increased queen loss, abnormal real cell production, weight loss, and reduced operculated brood [ 97 ].…”
Section: Main Causes Of Honeybee Colony Lossesmentioning
confidence: 69%
“…This leads to fewer honeybees returning to the colony, disorientation, or even a total loss of adult foragers (colony collapse disorder) ( 25 ). These negative effects of EMF could cascade into a number of additional effects on insects’ physiology and behavior, including less pollen and honey harvested ( 26 , 27 ), impaired learning ability, flight dynamics, foraging, and feeding ( 28 ), as well as increased piping in the colony ( 29 ). Hence, perturbations in terms of EMF from anthropic sources would disrupt the pollination services provided by honeybees, as they would avoid places exposed to EMF ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…This causes numerous foraging bees to lose their ability to return home [ 29 ]. Electromagnetic fields were therefore taken as one of the factors responsible for honeybee colony collapse disorder (CCD) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%